ANTIMICROBIAL ACTIVITY OF EXTRACTS OBTAINED FROM ANACARDIUM EXCELSUMAGAINTS SOME PATHOGENIC MICROORGANISMS - Celis, C.; García, A.; Sequeda, G.; Mendez, G.; Torrenegra, R. (Emirates Journal of Food and Agriculture, 2011)
In this study,we evaluated the antimicrobial activity of secondary metabolites presents in extracts and fractions of Anacardium excelsum (Anacardeaceae), using agar well diffusion assay and bioautography. As a general result was determined that Anacardium excelsum has good antimicrobial activity against gram positive microorganisms. Regarding the fractions in study, these were tested against Bacillus subtilis where the integument, seed and seed coat showed the best antimicrobial activity. Analysis by gas chromatography (GC) with mass selective detector (MSD) established the presence of some phenolic compounds like 2-(1,1-dimethylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, which is responsible of the activity found.